2014
DOI: 10.1021/tx500392n
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Air Particulate Matter (PM10) Exposure-Induced Ischemia-Like Injuries in the Rat Brain

Abstract: Epidemiological studies imply a significantly positive association between particulate matter (PM) level and ischemic stroke hospitalization. However, considering that PM10 is highly heterogeneous and varies with season within the same location, existing experimental evidence remained low. In the present study, we first treated Wistar rats with PM10 samples collected from different seasons in Taiyuan, a typically coal-burning city of China, and determined ischemia-related markers in the cortex. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The biological mechanisms by which pollutants could promote stroke are complex, and remained to be fully elucidated. In more simplified in vitro studies using cultures of neurons, astrocytes, and microglia have demonstrated increased susceptibility to oxygen and glucose deprivation [ 35 ], alteration in synaptic function [ 36 ] and upregulation in inflammatory cytokines [ 37 ] when exposed to PM air pollutants. However, in vitro studies are frequently performed by directly exposing cells to very high concentrations of PM.…”
Section: Experimental Evidence For the Association Between Air Pollutmentioning
confidence: 99%
“…The biological mechanisms by which pollutants could promote stroke are complex, and remained to be fully elucidated. In more simplified in vitro studies using cultures of neurons, astrocytes, and microglia have demonstrated increased susceptibility to oxygen and glucose deprivation [ 35 ], alteration in synaptic function [ 36 ] and upregulation in inflammatory cytokines [ 37 ] when exposed to PM air pollutants. However, in vitro studies are frequently performed by directly exposing cells to very high concentrations of PM.…”
Section: Experimental Evidence For the Association Between Air Pollutmentioning
confidence: 99%
“…Exposure of male rats to PM from pre-natal through adulthood increased cortical levels of the oxidative stress marker malondialdehyde and reduced levels of [superoxide dismutase]/[catalase] (60). In a study of ambient PM 10 exposure in rats, increases in cortical levels of IL-1β, iNOS, COX-2, ICAM-1 were found along with increases in TUNEL staining (78). Exposures of adult mice to re-aerosolized nanoPM increased levels of TNF-α, 4+NHe and 3-NT in olfactory epithelium and levels of IBA-1 in olfactory epithelium and olfactory bulb (79).…”
Section: Potential Mechanisms Of Cognitive Impairmentmentioning
confidence: 99%
“…The pooled relative risks were 1.011 for PM 2.5 , 1.002 for PM 10 , 1.015 for CO, 1.019 for SO 2 and 1.014 for NO 2 , respectively [ 39 ]. And the underlying mechanism by which air pollution exert as a risk factor for ischemic stroke might be that PMs and gaseous air pollutants, such SO 2 and NO 2 could activate astrocytes, disrupt synaptic functions and enhance endothelial and inflammatory responses of the brains [ 40 , 41 , 42 , 43 ]. Thus, to obtain more reliable and precise results, the potential air pollutants confounders should be taken into considerate.…”
Section: Discussionmentioning
confidence: 99%